Specific antibody deficiency in children with recurrent respiratory infections: a controlled study with follow‐up. (10th April 2013) - Ruuskanen, O.; Nurkka, A.; Helminen, M.; Viljanen, M. K.; Käyhty, H.; Kainulainen, L.
Summary Specific antibody deficiency (SAD) to unconjugated pneumococcal vaccine (PPV) is an established primary B cell immunodeficiency. The occurrence and natural history of SAD in children is unclear. We conducted an observational study to identify SAD in children with recurrent respiratory infections. Ninety‐nine children, mean age 5·9 (range 2–16) years, with recurrent or severe infections were vaccinated with PPV; serum antibody concentrations for serotypes 4, 6B, 9V, 14, 18C, 19F and 23F were measured before and 2 weeks after vaccination with enzyme immunoassay. The retrospective control group consisted of 89 healthy children matched for age and gender. No children had received previous conjugated pneumococcal vaccine (PCV) or PPV. The structured history of infectious diseases of all participants was collected. Ten of 91 (11%) children (eight excluded due to immunoglobulin G subclass deficiency) with recurrent respiratory infections had SAD. In the control group, three children (3%) responded inadequately to PPV (P = 0·05). Most children with SAD also had many other minor immune defects. After 0·5–5 years (medium 3·8), eight children with SAD were revaccinated with PPV; five responded adequately and three inadequately. Two SAD children were revaccinated with PCV, one developed an adequate and one an inadequate response. Two children with SAD received treatment with intravenous immunoglobulin; the remaining eight children recovered without replacement therapy during the follow‐up. SAD is common in young children with recurrent respiratory infections, but it is often transient and resolves itself within a few years without specific treatment.